Calycosin modulates inflammation via suppressing TLR4/NF‐κB pathway and promotes bone formation to ameliorate glucocorticoid‐induced osteonecrosis of the femoral head in rat. (23rd January 2021) - Zhu, Daoyu; Yu, Hongping; Liu, Pei; Yang, Qianhao; Chen, Yixuan; Luo, Pengbo; Zhang, Changqing; Gao, Youshui
Abstract : Glucocorticoid (GC) administration is one of the main causes of osteonecrosis of the femoral head (ONFH). Inflammation, especially the TLR4/NF‐κB pathway, has been demonstrated to play a pivotal role in the pathogenesis of GC‐induced ONFH. Calycosin, the main bioactive extract of Astragali Radix, could substantially regulate the TLR4/NF‐κB pathway. Therefore, in this study, we hypothesized that calycosin could exert beneficial effects in GC‐induced ONFH. In vitro, effects of calycosin on the osteogenic differentiation of human bone mesenchymal stem cells (hBMSCs) were determined using Alizarin red staining, alkaline phosphatase activity examination, and osteogenic‐related gene assay. Meanwhile, inflammatory cytokines were detected by enzyme‐linked immunosorbent assay. In vivo, 60 male Sprague–Dawley rats were randomly separated into three groups: the control group, the methylprednisolone (MPS) group, and the MPS + calycosin group. The results showed that calycosin could significantly promote dynamic bone formation and retard TLR4/NF‐κB pathway. in vivo investigations indicated that calycosin could decrease the morbidity of ONFH and alleviate pathological manifestations within the femoral head. Meanwhile, calycosin could protect osseous blood supply and facilitate dynamic bone formation. The findings collectively demonstrated that calycosin could ameliorate GC‐induced ONFH in rat and might become a potential candidate for pharmaceutical prevention of this intractable disease.